Light at night negatively affects mood in diurnal primate-like tree shrews via a visual pathway related to the perihabenular nucleus - Ying Miao; Huan Zhao; Yu-Fei Li; Yan-Ping Sun; Rui Bi; Hongli Li; Xin Fang; Zi-Shuo Li; Yu-Hua Ma; Long-Bao Lv; Kai An; Jian-Jun Meng; et al. (Proceedings of the National Academy of Sciences, 2025)
To better understand the potential health threats and underlying visual pathways of long-term light at night (LAN) exposure, we adopted a widely accepted diurnal animal model tree shrew ( Tupaia belangeri chinensis ), which is a close relative to primates, and evaluated the deleterious effects of long-term LAN exposure. We used an early-night LAN paradigm that was established in mice to examine behavioral and physiological consequences in adult male tree shrews. We found that 3-wk LAN exposure significantly impaired the mood and long-term memory of tree shrews without affecting the general activity pattern. We identified retinal projections to the perihabenular nucleus (pHb), a crucial area in LAN-induced negative mood, and demonstrated that the pHb continues to innervate the nucleus accumbens (NAc) in tree shrews. Moreover, the pHb was required for the LAN effect on mood but not long-term memory. Transcriptomic profiling of brain tissues containing the NAc area revealed drastic changes of several depression-related genes in NAc neurons post-LAN treatment, suggesting that long-term exposure to nighttime light could result in lasting changes in tree shrews. Collectively, we present behavioral and neural structural evidence that LAN exerts depression-inducing effects in diurnal animals via a pHb-related visual pathway, which may facilitate the translation from laboratory findings of excessive LAN exposure to clinical applications in humans.